A Transtheoretical Model-Based Online Intervention to Improve Medication Adherence for Chinese Adults Newly Diagnosed With Type 2 Diabetes: A Mixed-Method Study - Baolu Zhang; Surintorn Kalampakorn; Arpaporn Powwattana; Jutatip Sillabutra; Gang Liu (SAGE Publishing, 2024)
Background: Type 2 diabetes mellitus (T2DM) is increasing in China, with medication non-adherence being a significant contributor to uncontrolled T2DM. The Transtheoretical Model (TTM) has shown effectiveness in chronic disease management, but few studies have applied it in online interventions for T2DM medication adherence. Aim: The study aimed to develop and investigate the effects of a TTM-based online health education program on promoting positive stage of change (SOC) movement, improving self-efficacy and medication adherence, as well as reducing HbA1c levels in newly diagnosed patients with T2DM. Methods: This sequential mixed-method study was conducted from April 2023 to March 2024. Using the TTM framework, the study initially explored 32 participants' experiences with hypoglycemic medications, health information acquisition, and perspectives on online programs. Then, a quasi-experimental study design was conducted. Two communities were randomly assigned as the intervention (n = 91) and comparison (n = 98) groups, with 189 newly diagnosed middle-aged T2DM patients from various SOC. The intervention group received short videos health education and participated in WeChat group discussions, compared with usual care in the comparison group. Data were collected at baseline, 3-month, and 6-month follow-ups. Results: The intervention group was more likely to achieve positive SOC movement ( P  < .001, Adj OR = 13.69 95% CI = 6.76-27.71) compared to the comparison group. The intervention group also had significantly higher mean CDMSS-11 and MMAS-8 scores at 6 months ( P  = .03 and <.001, respectively) and more likely to achieve clinically significant glycated Hemoglobin (HbA1c) change at 3 months ( P  < .001, Adj OR = 3.91, 95% CI = 1.77-8.63) and at 6 months ( P  < .001, Adj OR = 5.62, 95% CI = 2.70-11.69) compared to the comparison group. Conclusion: These findings support that applying the TTM to develop an online program could promote behavior change, improve self-efficacy and medication adherence, and could lead to better glycemic control in newly diagnosed T2DM patients.